2015
DOI: 10.1007/s00253-015-6652-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a protective mouse monoclonal antibody against human enterovirus 71

Abstract: Human enterovirus 71 (EV71) infection has emerged as a major threat to children; however, no effective antiviral treatment or vaccine is currently available. Antibody-based treatment shows promises to control this growing public health problem of EV71 infection, and a few potent monoclonal antibodies (mAbs) targeting viral capsid protein have been well described. Here, we generated an EV71-specific mouse mAb 2G8 that conferred full protection against lethal EV71 challenge in a suckling mouse model. 2G8 belonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Monoclonal antibody therapy could be an alternative to IVIg. Monoclonal antibodies are highly specific and bind to highly conserved regions present in all subgenotypes of EV‐A71 . The identified neutralizing antibodies listed by Ng et al could also be further developed into humanized antibodies for therapeutic use.…”
Section: Prevention and Control: How Close We Are To Success?mentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibody therapy could be an alternative to IVIg. Monoclonal antibodies are highly specific and bind to highly conserved regions present in all subgenotypes of EV‐A71 . The identified neutralizing antibodies listed by Ng et al could also be further developed into humanized antibodies for therapeutic use.…”
Section: Prevention and Control: How Close We Are To Success?mentioning
confidence: 99%
“…Monoclonal antibodies are highly specific and bind to highly conserved regions present in all subgenotypes of EV-A71. [150][151][152][153][154][155] The identified neutralizing antibodies listed by Ng et al 147 could also be further developed into humanized antibodies for therapeutic use. Other immune modulators such as IFN-α and IL-18…”
Section: Il-6 Is An Interleukin Secreted By Macrophages and T Lymphocmentioning
confidence: 99%
“…The synthetic peptide SP70, located at amino acids 208–222 in VP1, has been identified as a neutralizing and protective EV-A71-specific B-cell epitope in animals [16,22,48]. Several studies have demonstrated that neutralizing mAbs generated by EV-A71-immunized mice can recognize SP70 [1720,22]. In addition, VP2-28 (amino acids 136–150 in VP2) is a cross-neutralization epitope recognized by commercial mAb 979 and mAbs generated by immunized mice [22, 2,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are disadvantages to using pooled human sera, such as the risk of transmitting human pathogens, availability of donors, and batch-to-batch variability [19]. Therefore, neutralizing monoclonal antibodies (mAbs) are considered a safe alternative for passive immunization against EV71.Over the years, several EV71-neutralizing antibodies have been reported [20][21][22][23][24][25][26]. Among these mAbs, D5 is one of the most promising mAb for development as prophylactic and therapeutic for EV71 infection.…”
mentioning
confidence: 99%
“…Over the years, several EV71-neutralizing antibodies have been reported [20][21][22][23][24][25][26]. Among these mAbs, D5 is one of the most promising mAb for development as prophylactic and therapeutic for EV71 infection.…”
mentioning
confidence: 99%